2013
DOI: 10.1103/physrevlett.110.168301
|View full text |Cite
|
Sign up to set email alerts
|

Creep Measurements Confirm Steady Flow after Stress Maximum in Extension of Branched Polymer Melts

Abstract: We provide conclusive evidence of nonmonotonic mechanical behavior in the extension of long-chain branched polymer melts. While nonmonotonic behavior is known to occur for solids, for the case of polymeric melts, this phenomenon is in direct contrast with current theoretical models. We rule out the possibility of the overshoot being an experimental artifact by confirming the existence of steady flow after a maximum in the ratio of stress to strain rate versus strain under both constant stress and constant stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 21 publications
(29 reference statements)
2
32
0
Order By: Relevance
“…Figure 6 also shows that at fast strain rate, the extensional steadystate viscosity exhibits a power-law behavior with the viscosity scaling approximately asε −0.6 , which agrees with the observations reported in Ref. [11,13]. It should be noted that the identical nonlinear behavior is only observed at Hencky strain values bigger than 4 as shown in Figure 5(b), which cannot be measured by the EVF.…”
Section: Startup and Steady-state Extensional Flowsupporting
confidence: 80%
See 1 more Smart Citation
“…Figure 6 also shows that at fast strain rate, the extensional steadystate viscosity exhibits a power-law behavior with the viscosity scaling approximately asε −0.6 , which agrees with the observations reported in Ref. [11,13]. It should be noted that the identical nonlinear behavior is only observed at Hencky strain values bigger than 4 as shown in Figure 5(b), which cannot be measured by the EVF.…”
Section: Startup and Steady-state Extensional Flowsupporting
confidence: 80%
“…A maximum in the transient extensional stress of LDPE was observed by several groups [8,9,10]. Steady stress following the stress overshoot was reported firstly by Rasmussen et al [11] and has been experimentally confirmed by comparing the measurements from the filament stretching rheometer and the cross-slot extensional rheometer [12], as well as by comparing the constant stretch rate and constant stress (creep) experiments [13]. Several models have been developed [12,14,15] for the attempt to understand the physics behind the stress overshoot.…”
Section: Introductionmentioning
confidence: 84%
“…A stress maximum has been reported in extensional flow of branched polymers [173], analogous to the stress maximum in entangled linear polymers in transient shear flow. In the case of long chain branched polyethylene, for example, Hoyle et al [183] demonstrated and inferred a stress maximum followed by a steady state condition, by using both the FSR device and the cross-slot rheometer.…”
Section: Uniaxial Extensional Flows: Strain Hardening Overshoot and mentioning
confidence: 70%
“…Furthermore, we remark that the extensional data do not show a tendency to overlap the dynamic and shear data at low rates, as is normally expected. However, it is reported that for branched polymers the steady viscosity in uniaxial extension is constant at low stretch rate (overlaps with 3 *), then it exhibits extension thickening and after an overshoot it thins at higher rates [59]. Based on this, we conjecture that the data of Figure 7 are in the thinning regime past but close to the peak, and they are above the level of the zero-rate viscosity (not reached) which is expected to coincide with the zero-shear dynamic and shear viscosities, accounting for the Trouton ratio.…”
Section: Resultsmentioning
confidence: 99%